Pengaruh Ukuran Perusahaan, Struktur Modal, Return On Asset, dan Total Asset Turnover terhadap Pertumbuhan Laba - Nally Indirawati; Said Said; Maulida Kiatuddin (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2026)
The property and real estate sub-sector serves as a strategic pillar for investment in Indonesia, despite BPS (2023) data showing a growth slowdown to 2.18% due to macroeconomic pressures. Financial performance throughout the 2021–2024 period exhibited significant volatility, with profit growth contracting to –5% in 2022 before rebounding to 15% in 2024. These fluctuations reflect the dynamics of economic recovery and the success of corporate operational efficiency in navigating interest rate hikes and inflation. This study aims to determine the effect of Company Size, Capital Structure, Return on Assets (ROA), and Total Asset Turnover (TATO) on Profit Growth. The population used in this study is the Property & Real Estate sub-sector companies listed on the Indonesia Stock Exchange for the 2021–2024 period. This study uses secondary data with a population of 68 companies. The sampling technique used a purposive sampling technique, resulting in a research sample of 30 Property & Real Estate sub-sector companies. The analysis technique used is multiple linear regression analysis processed using the Statistical Package for the Social Sciences (SPSS) program. The results show that Capital Structure, Return on Assets, Total Asset Turnover, and Company Size influence Profit Growth.